ANALYTIC OF TWO-DIMENSIONAL FIGURE WITH DEVIATION ANGLE - HIJRIAH (NIM: 10114060), ALIP
Geometry is one of the oldest branches of mathematics. Nevertheless, there are still some different opinions regarding the sides and the vertices of a shape, for example how many sides and vertices in a circle. In this final project, a new concept will be introduced namely the deviation angle that is defined as the angle between the reference vector v_A with the vector . This final project thesis will discuss about the deviation angle on convex and non-convex two-dimensional figures. The deviation angle of a circle which the observers point lies around the boundary of the circle curve will be discussed. Then, it will be shown that the number of vertices is equal to the number of singular points on a two-dimensional figure and the number of sides is equal to the number of smooth curves on a two-dimensional figure. Thus, for example, it can be proved that the number of vertices the circle is equal to zero and the number of sides on the circle is equal to one.